Analisis Kepuasan Pengguna Aplikasi Manajemen Surat (AMS) di PT PLN (Persero) UP3 Palembang Menggunakan Metode End User Computing Satisfaction (EUCS) - Linra, Afriani; Effendy, Irman; Mutatkin, Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The use of computer technology as an information technology tool for companies provides added value to the data processing process, the existence of information technology is also very useful for companies to facilitate performance in daily activities, especially as support in PLN official correspondence, both internal and external correspondence, starting from Service Notes, Letters, Special Form Letters and Legal Products. To keep up with technological advances, PT PLN (Persero) uses the Corporate Mail Management Application (AMS) to support business processes that provide an advantage for the company in achieving its goals. By using this application, PLN can manage letters automatically as well as manage electronic archives which benefits employees, thereby increasing the satisfaction of users of the application. User satisfaction with system performance is a benchmark for implementing information technology. This research uses the End User Computing Satisfaction (EUCS) method to determine user satisfaction of the Mail Management Application (AMS) at PT PLN (Persero) UP3 Palembang. The factors used in the EUCS method include Content, Format, Accuracy, Ease of Use, and Timeliness. Data collection was carried out by conducting a survey of 120 employees of PT PLN (Persero) UP3 Palembang, the results of which were analyzed using the IBM SPSS Version 25 application.